KAMITA: A WEB-BASED INTERACTIVE MEDIA TO INTRODUCE “KAMI” & “KITA” DIFFERENCES TO THE 1st-3rd GRADER IN SDN SAMPETAN - Adhitya Amarulloh; Rima Yunika Pratiwi; Arsyananda Rabbani (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
The distinction between the Indonesian pronouns